2016
DOI: 10.1016/j.celrep.2015.12.025
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Analysis of the Cdk13/Cyclin K Complex

Abstract: Cyclin-dependent kinases regulate the cell cycle and transcription in higher eukaryotes. We have determined the crystal structure of the transcription kinase Cdk13 and its Cyclin K subunit at 2.0 Å resolution. Cdk13 contains a C-terminal extension helix composed of a polybasic cluster and a DCHEL motif that interacts with the bound ATP. Cdk13/CycK phosphorylates both Ser5 and Ser2 of the RNA polymerase II C-terminal domain (CTD) with a preference for Ser7 pre-phosphorylations at a C-terminal position. The pept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
140
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(150 citation statements)
references
References 40 publications
10
140
0
Order By: Relevance
“…CDK12 and its homolog CDK13 (containing a virtually identical kinase domain) associate with CCNK to form two functionally distinct complexes CCNK/CDK12 and CCNK/CDK13 . Transcription of several core homologous recombination (HR) DNA repair genes, including BRCA1, FANCD2, FANCI, and ATR, is CDK12‐dependent . In agreement, treatment with low concentrations of THZ531 resulted in down‐regulation of a subset of DNA repair pathway genes.…”
Section: Introductionmentioning
confidence: 79%
“…CDK12 and its homolog CDK13 (containing a virtually identical kinase domain) associate with CCNK to form two functionally distinct complexes CCNK/CDK12 and CCNK/CDK13 . Transcription of several core homologous recombination (HR) DNA repair genes, including BRCA1, FANCD2, FANCI, and ATR, is CDK12‐dependent . In agreement, treatment with low concentrations of THZ531 resulted in down‐regulation of a subset of DNA repair pathway genes.…”
Section: Introductionmentioning
confidence: 79%
“…They are involved in gene transcription and Pre-mRNA Splicing [22][23][24]. Recent studies have shown that aberrant levels of CDK13 were associated with several cancers.…”
Section: Discussionmentioning
confidence: 99%
“…The family contains 20 members which can be divided into the cell‐cycle kinases (including CDK1,2,3,4, and 6) and the transcriptional CDKs (including CDK12, 13, 9, 8, and 7) . CDK12 is very closely related and highly homologous to CDK13, and the ATP binding sites of these proteins are essentially identical; however, knockdown of CDK13 affects different genes compared to CDK12, having effects on growth signaling pathways . From the outset, we concluded that selectivity between CDK12 and CDK13 would be extremely difficult to obtain, so we initially focused on obtaining selectivity over CDK9 and CDK7 as transcriptional CDKs, and CDK2 and 1 as representative and well‐known examples of the cell‐cycle CDKs.…”
Section: Published Pan‐cdk Inhibitor Dinaciclib and Dual Ck1δ/ck1ϵ Inmentioning
confidence: 99%